Aplikasi Metode Aktivasi Secara Kimia dan Fisika, Pada Zeolit Alam Sebagai Penejrap Logam Dalam Proses Pemurnian Air - Puput Eka Suryani (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2021)
Based on the method of formation, zeolites can be divided into two types, namely natural zeolites and artificial zeolites. Natural zeolites are zeolites that are formed naturally due to natural changes or from volcanic rocks due to volcanic eruptions. Natural zeolite can be applied as an adsorption system after the activation process. Activation of natural zeolite can be done in several ways, namely by acid washing method, which is then referred to as chemical activation. In addition, hydrothermal treatment can also be used as an activation method for zeolite preparation. The hydrothermal method is a high temperature heating method to remove water content as well as impurities in the zeolite. In this study, chemical and physical activation processes will be carried out to increase the crystallinity of the zeolite. In its application, the zeolite adsorption process will be carried out on water samples. From the XRD data, the treatment or physical modification of natural zeolite was able to increase the crystallinity significantly. Prior to the modification of the XRD data at an angle measurement of 2θ : 10-90 deg, the peaks were quite sharp. The percentage result shows that the sample before the modification reached 81.87%. Washing with distilled water has been able to increase the level of crystallinity which is quite significant. In the modified zeolite with the same analysis, the percentage of crystallinity was 99.24%.